Underwater Transmitted Wavefront Manipulation Based on Bubble-Arrayed Acoustic Metasurfaces - Li, Zhimin; Lin, Zibin; Zeng, Longsheng; Wu, Hao; Zhu, Xue-Feng (Frontiers in Physics, 2022)
Manipulating underwater acoustic waves along the prescribed trajectory has great potential for various applications. Traditional metasurfaces for underwater acoustic modulation usually have complex structural designs and are complicated to manufacture. Here, we propose a simple strategy by embedding air bubbles of different sizes inside the polymer to freely manipulate the transmitted underwater acoustic wave fields. The transmitted phase shift covers the entire 2π range by adjusting the diameter of the bubbles. Utilizing the air-bubble array with precisely designed phase profiles, the abnormal refraction, self-bending beams, and bottle beams are univocally demonstrated based on the generalized Snell’s law. Our study can be used for designing waterborne metasurfaces with simple structures to freely manipulate the transmitted wavefronts and inspire lots of applications for the underwater exploration.